THE ESSENCE OF MENTAL TRAINING AND OPPORTUNITIES FOR ITS USE IN THE VIOLIN TEACHING AND LEARNING PROCESS OF PUPILS IN PRIMARY SCHOOL EDUCATION - Mērija Vilnīte, Fiona; Marnauza, Māra (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2015)
The subject of mental training has gained a great deal of attention in the field of sports psychology and various authors have shown that many of the components of mental training transfer successfully to a musical setting (Green, Gallwey, 2012). Yet the explanations for its success, why this may depend on certain conditions and whether there are special considerations for musicians, have remained relatively obscure (Johnson, 2003). Additionally, mental training is more frequently used in both sports and music with already-trained practitioners; the few studies that explore the components of mental training with children are currently in the field of sport (e.g. Orlick, McCaffrey, 1991; Julien, 2002; Li-Wei et al, 1992) and therefore do not address the specifics of learning a musical instrument. The aim of this paper is to investigate the premise of mental training and to assess opportunities for its use in the one-to-one violin teaching and learning process of primary school-aged pupils. The applied methods: Analysis of the scientific literature on mental training, its connections to literature in neuroscience and primary school age-related studies; teaching observations. Relevant conclusions: Children from a young age have mental imagery abilities and there are opportunities for the use of mental training in the violin teaching and learning process of pupils in the primary school age group. A synthesis of the literature on mental training, neuroscience and empirical teaching observations suggests that for mental training to be most beneficial, it should be introduced consciously and purposefully within the teaching and learning process.